Memory as Burden and Liberation : Germans and their Nazi Past (1945-2010) - Wolff-Poweska, Anna (2014)
This book examines both the obvious and less obvious ways in which Germans struggle with their Nazi past. It embraces only a small part of a complex problem, which is impossible for an individual author to grasp in its entirety and character. The main intention, which leads through a thick of actors, issues, institutions, events and phenomena, is a reflection upon the reasons for which German reckoning with the past turned out to be a process full of contradictions; a bumpy road rippled with political, intellectual and moral mines. This intention is accompanied by the question about the specific character of German collective memory in relation to the helplessness and moral condition of a person defending himself/herself and his/her nation in the face of unimaginable evil.